2007
DOI: 10.1111/j.1440-1827.2007.02137.x
|View full text |Cite
|
Sign up to set email alerts
|

MUC2, MUC5AC and MUC5B in the mucus of a patient with pseudomyxoma peritonei: Biochemical and immunohistochemical study

Abstract: A 58-year-old man with a 1 year history of progressive abdominal distension underwent a laparotomy for pseudomyxoma peritonei. The mucin was identified and characterized in the present study. Approximately 6 L of crude mucus in the sol (highly viscous) and gel (semisolid) phases was obtained from the patient's peritoneal cavity. The sol material was briefly homogenized followed by slow stirring at dilutions of up to 1:10 with 6 mol/L guanidinium chloride and proteolytic inhibitors for periods of up to 48 h. Pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 45 publications
2
30
0
3
Order By: Relevance
“…The prognostic significance of MUC2 is reported to be controversial, as the expression level of MUC2 in PMP is independent of the degree of the malignant transformation [130]. The presence of MUC5B, in addition to MUC2 and MUC5AC was reported in case studies of PMP subjects [131,132], investigations by Sheehan et al implicated a low-charge glycoform of MUC5B in the production of a tenacious respiratory mucus plug [133,134], it may be MUC5B as speculated by Mall et al that is responsible for the semisolid material found in some PMP patients. The development of mucin-targeted therapies was suggested by Amini et al [127] which could be a promising avenue for future research based on the relevance of MUC2, MUC5AC and MUC5B in PMP.…”
Section: Pseudomyxoma Peritoneimentioning
confidence: 98%
“…The prognostic significance of MUC2 is reported to be controversial, as the expression level of MUC2 in PMP is independent of the degree of the malignant transformation [130]. The presence of MUC5B, in addition to MUC2 and MUC5AC was reported in case studies of PMP subjects [131,132], investigations by Sheehan et al implicated a low-charge glycoform of MUC5B in the production of a tenacious respiratory mucus plug [133,134], it may be MUC5B as speculated by Mall et al that is responsible for the semisolid material found in some PMP patients. The development of mucin-targeted therapies was suggested by Amini et al [127] which could be a promising avenue for future research based on the relevance of MUC2, MUC5AC and MUC5B in PMP.…”
Section: Pseudomyxoma Peritoneimentioning
confidence: 98%
“…In two case studies, Mall et al reported the presence of MUC5B, in addition to MUC2 and MUC5AC, in the PMP material [122,123]. Based on the investigations by Sheehan et al implicating a low-charge glycoform of MUC5B in the production of a tenacious respiratory mucus plug [124,125], Mall et al speculated that it may be MUC5B that is responsible for the semisolid material found in some PMP patients.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the investigations by Sheehan et al implicating a low-charge glycoform of MUC5B in the production of a tenacious respiratory mucus plug [124,125], Mall et al speculated that it may be MUC5B that is responsible for the semisolid material found in some PMP patients. Given the high protein content of the PMP secretions, they also raised the possibility that interactions between mucin and non-mucin proteins could contribute to the viscous nature of the PMP exudates [122,123]. Table 3 summarizes a number of studies in which disease-specific expression pattern of MUC2 and other mucins in PMP has been explored.…”
Section: Introductionmentioning
confidence: 99%
“…It has previously been reported that pseudomyxoma peritonei (PMP), which was first described in 1842, is a disease of MUC2-expressing goblet cells, although the copious intraperitoneal mucinous ascites containing huge globules of extracellular mucin [11, 12] may also contain MUC5AC [13]. The accumulation of large amounts of extracellular mucus in the abdominal cavity is probably the main cause of the disease's morbidity and mortality, irrespective of the site of origin [12].…”
Section: Introductionmentioning
confidence: 99%
“…The accumulation of large amounts of extracellular mucus in the abdominal cavity is probably the main cause of the disease's morbidity and mortality, irrespective of the site of origin [12]. The first and only report, to our knowledge, of the presence of MUC5B in tissue and gelatinous material of a 58-year-old male diagnosed with PMP was from our laboratory [13]. The expression of MUC2 in PMP accounts for both the voluminous deposits of extracellular mucus and in women would help distinguish the appendix rather than the ovary as the site of origin of the disease [14].…”
Section: Introductionmentioning
confidence: 99%